A New Form for a New People: Forugh Farrokhzad's The House Is Black - Saljoughi, Sara (Camera Obscura: Feminism, Culture, and Media Studies, 2017)
This article examines the problem of collectivity in Forugh Farrokhzad's The House Is Black (Khaneh siah ast, Iran, 1962), an experimental film set in a leper colony in northwestern Iran. Focusing on the film's experiments with form, the article explores how the development of new relations between sound and image corresponds with the projection of a collectivity to come. The article argues that the film does not seek to humanize the members of the leper colony but rather to radically rethink the relation between the filmmaker and the subjects of the film. This new relationship as a model for collectivity is analyzed in tandem with a reading of Pier Paolo Pasolini's 1965 essay “The Cinema of Poetry.” The article examines several of the film's formal strategies, such as the mobilization of the female authorial voice, in discussing how the film engages with and expands on the notion of the cinema of poetry. It argues that the techniques used by Farrokhzad are key to the development of a new film form in Iran.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTIxNS8wMjcwNTM0Ni0zNjYxOTgy